Barriers and Facilitators to Sustaining School Health Teams in Coordinated School Health Programs. Issue 3 (May 2017) - Cheung, Karen; Lesesne, Catherine A.; Rasberry, Catherine N.; Kroupa, Elizabeth; Fisher, Deborah; Robin, Leah; Pitt Barnes, Seraphine
Coordinated school health (CSH) programs address multiple factors related to students' overall health, thereby increasing their physical and mental readiness to learn. A formative evaluation of three school districts in 2010-2011 examined strategies for sustaining the school health teams (SHTs) that lead CSH efforts. Qualitative data from 39 interviews and 13 focus groups revealed facilitators and barriers for sustaining SHTs. Quantitative data from 68 questionnaires completed by SHT members and school principals examined factors associated with having more active SHTs and district and school characteristics SHT members believed to be important to their schools' efforts to implement CSH. Facilitators of sustaining SHTs included administrative support, staff engagement in the SHT, and shared goals and responsibility. Barriers to sustaining SHTs included limited time and competing priorities, budget and funding constraints, and staff turnover. Findings provide valuable insight into challenges and potential solutions for improving the sustainability of SHTs to enable them to better support CSH efforts.